Reported Sexual-offense Incidents in the United States: Arrest Disparities between Women and Men - Shaw, Callie Dara (Journal of interpersonal violence, 2022)
This study examined the effect of an offender?s sex (male/female) on whether sexual-offense incidents reported to law enforcement culminated in an arrest. Two hypotheses, chivalry and evil woman, are relied upon and suggest that the probability of arrest differs for women and men, yet in differing directions. The chivalry hypothesis suggests women are treated more leniently than men and, therefore, less likely to be arrested. The evil woman hypothesis, however, suggests the opposite: Women are treated more harshly than men and, therefore, more likely to be arrested. Seven years of National Incident-based Reporting System [NIBRS] data were relied upon (National Archive of Criminal Justice Data, 2010?2016, National Incident-based Reporting System: Extract Files); all of the reported sexual-offense incidents committed by women were included, along with a matched sample of reported sexual-offense incidents committed by men, culminating in a sample of 22,744. Overall, women were 42% significantly less likely than men to be arrested when controlling for other known offense, offender, and victim characteristics. The odds for women to be arrested increased, however, when specific offender demographics, offense characteristics, and victim characteristics were taken into account. The implications of these findings are discussed in regard to their application of the chivalry and evil woman hypotheses.